The Relationship Between ESG Performance and Investment Efficiency: A Systematic Literature Review - Khalida Utami; Salis Musta’ani; Syamsul Bahri; Salma Atikah (Jurnal Greenation Ilmu Akuntansi, 2026)
The relationship between Environmental, Social, and Governance (ESG) performance and Investment Efficiency (IE) is an important issue in modern corporate finance. IE reflects a company's ability to allocate capital optimally, while investment inefficiency is often influenced by information asymmetry and agency conflicts. To provide a more integrated understanding, this study conducted a Systematic Literature Review (SLR) based on the PRISMA protocol by analyzing 26 articles from Scopus and ScienceDirect on September 30, 2025. The SLR results show that research is dominated by Agency Theory, Stakeholder Theory, and Signaling/Information Asymmetry Theory, with a tendency toward an increase in advanced econometric causality approaches. Publications increased rapidly in 2024–2025. In general, there is a strong consensus that ESG performance has a positive effect on IE through the reduction of information asymmetry, financing constraints, and agency costs. However, this effect may vary depending on the institutional context and the reliability of ESG measurements. Research gaps still exist in the context of developing countries, testing transmission mechanisms, and the accuracy of ESG score measurements. These findings confirm that ESG is a strategic asset for companies to improve transparency, capital allocation efficiency.